Comparative study of serum levels of Perforin in Prostate Cancer and Benign Prostatic Hyperplasia patients - Mohammadzade, Jahangir; Amirrasouli, Houshang; Akbari, Mohammad Esmaeil; Javanmard, Babak; Kazerouni, Faranak; Namaki, Saeed; Rahimipour, Ali; Tahbaz lahafi, Behnoosh; Mahdavi, Meisam; Sedighi Moghadam, Alireza (Archives of Advances in Biosciences, 2013)
Perforin(p) is the primary mediator of short term cytotoxicity, it is accumulated in response to proinflammatory cytokines and stored in T lymphocyte , NK cells and NKT cells are released upon activation. Perforin is a prototypical cytotoxic molecule involved in cell mediated immunity against various pathogens , alloantigens and particularly different tumors.The purpose of this study was to determine perforin level in prostate cancer (P.Ca) and Benign Prostatic Hyperplasia (BPH) This is study was performed on 59 patients consisting of 28 patients with P.Ca and 31 patients with BPH.Perforin and PSA levels were measured in cancer and BPH patients using ELISA method. Mean Perforin value was significantly lower in P.Ca patients than in BPH patients ( p < 0.01) where as mean serum PSA level was significantly higher in the cancer patients in comparison to the BPH group (P < 0.01 Our finding indicate probability of problem in expression of cytotoxic molecule ,perforin in and around the tumor.